Regional Development or Regional Policies? A Review of 60 Years of Regional Planning and Development in Pre and Post Islamic Revolution Iran - Musa Pajoohan (The Institute for Research and Community Services, Institut Teknologi Bandung, 2019)
Since the emergence of planning thought 90 years ago, planning and development in Iran has always been a subject of active debate. Despite this long history, the centralized planning system has never been able to promote development that is consistent with the advantages and disadvantages of the regions, hence the evident imbalance in regional development of the country. This article aims to investigate the obstacles to regional development in Iran before and after the 1979 revolution, using a descriptive-analytic methodology. The results show that the main obstacle in regional development in the country lies in its centralized management and planning system, having led to serious barriers such as a sectoral approach in regional planning and management system, lack of a legal status for regional development, dependence on oil revenues, and lack of data and information resources. Abstrak. Sejak kemunculan pemikiran perencanaan 90 tahun yang lalu, perencanaan dan pembangunan di Iran selalu menjadi subjek perdebatan yang aktif. Terlepas dari sejarah yang panjang ini, sistem perencanaan yang sentralistik tidak pernah mampu mempromosikan pembangunan yang konsisten dengan kekuatan dan kelemahan wilayah tersebut, dan juga pengembangan wilayah yang timpang di negara tersebut. Artikel ini bertujuan untuk menyelidiki hambatan dalam pengembangan wilayah di Iran sebelum dan sesudah revolusi 1979, menggunakan metodologi deskriptif-analitik. Hasil penelitian menunjukkan bahwa hambatan utama dalam pengembangan wilayah di negara ini terletak pada sistem manajemen dan perencanaan yang terpusat, yang menyebabkan hambatan serius seperti pendekatan sektoral dalam perencanaan wilayah dan sistem manajemen, kurangnya dasar hukum untuk pengembangan wilayah, ketergantungan pada pendapatan minyak, dan kurangnya sumber daya data dan informasi.Kata Kunci. Perencanaan dan pengembangan wilayah, hambatan dan rintangan, sistem perencanaan nasional, Iran.